Educational product: residential automation with Arduino and IoT (Research, Society and Development, 2022)
Interdisciplinarity allows for the integration of knowledge, strengthening the interdependence between disciplines and global integration. The research uses the concept of Domotics and integrates the theoretical and the practical, as well as science and technology to automate a model. Thus, the goal of the research is to present the development of an educational product, in the format of a residential model, which performs the automation of tasks and controls remotely, via smartphone, the equipment and devices contained in it. For this, the Arduino microcontroller was used to obtain practical, didactic and low-cost applications to facilitate the teaching-learning of students. This integration strengthens the assimilation of the concepts obtained in the theoretical classes by establishing relationships between knowledge, both from the technical and undergraduate courses. The Internet of Things concept and the Blynk software were used to perform all activations remotely, via smartphone. The results were satisfactory and all the equipment worked as expected within the scope of the work.